2021
DOI: 10.1155/2021/4226141
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pediatric Onset Multiple Sclerosis in Saudi Arabia

Abstract: Background. The prevalence of multiple sclerosis (MS) appears to be increasing worldwide. However, data on the pediatric onset of MS is lacking, particularly in developing countries. Objective. This study is aimed at reporting the current burden of the pediatric onset of MS in the five regions of Saudi Arabia. Methods. This study used relevant data from the National Saudi MS Registry that was operational between 2015 and 2018. The data on patients with pediatric onset MS from all the hospitals included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…10 From 2015 to 2018, the first nationwide multicenter MS registry was initiated in KSA, mainly to describe the current epidemiology, disease patterns, and clinical characteristics of MS in KSA. 11 The data reported a high rampancy of MS in KSA, which is alarming and warrants immediate public health action. A local study showed that the projected prevalence of MS was estimated at 40.40/100,000 total population putting KSA above the low-risk zone as per Kurtzke classification.…”
Section: Introductionmentioning
confidence: 95%
“…10 From 2015 to 2018, the first nationwide multicenter MS registry was initiated in KSA, mainly to describe the current epidemiology, disease patterns, and clinical characteristics of MS in KSA. 11 The data reported a high rampancy of MS in KSA, which is alarming and warrants immediate public health action. A local study showed that the projected prevalence of MS was estimated at 40.40/100,000 total population putting KSA above the low-risk zone as per Kurtzke classification.…”
Section: Introductionmentioning
confidence: 95%
“…In a recent paper, Bunyan and coworkers (2021) [18], utilizing the Saudi National Registry, estimated the prevalence of pediatric MS to be 2.73/100,000 of the Saudi pediatric population, and the overall projected prevalence was estimated to be 14.33/100,000 of the Saudi pediatric population. There were 287 MS pediatric patients in the register with a median age at diagnosis of 16.0 years, and girls were more prevalent than boys (female 74.2%; male 25.8%) [18].…”
Section: Epidemiologymentioning
confidence: 99%
“…Women are more likely than men to have MS, and this incidence has increased over the past few years [22,23]. MS primarily affects adolescents, most often manifesting between 20 and 40 years of age, but it can also develop in children before the age of 18 [24].…”
Section: Introductionmentioning
confidence: 99%